Business Creation and the Stock Market - Michelacci, Claudio; Suarez, Javier (Review of Economic Studies, 2004)
We claim that the stock market encourages business creation, innovation, and growth by allowing the recycling of “informed capital”. Due to incentive and information problems, start-ups face larger costs of going public than mature firms. Sustaining a tight relationship with a monitor (bank, venture capitalist) allows them to finance their operations without going public until profitability prospects are clearer or incentive problems are less severe. However, the earlier young firms go public, the quicker monitors' informed capital is redirected towards new start-ups. Hence, when informed capital is in limited supply, factors that lower the costs for start-ups to go public encourage business creation. Technological spill-overs associated with business creation and thick market externalities in the young firms segment of the stock market provide prima facie cases for encouraging young firms to go public.